2016
DOI: 10.1016/j.jns.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms and cognitive decline in Parkinson's disease

Abstract: We and others have suggested that vitamin D receptor gene (VDR) polymorphisms influence susceptibility for Parkinson’s disease (PD), Alzheimer’s disease (AD), mild cognitive impairment (MCI) or overall cognitive functioning. Here we examine VDR polymorphisms and cognitive decline in patients with PD. Non-Hispanic Caucasian PD patients (n=190) in the Parkinson Environment Gene (PEG) study were successfully genotyped for seven VDR polymorphisms. Cognitive function was assessed with the Mini-Mental State Exam (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 83 publications
1
21
0
1
Order By: Relevance
“…In addition, recent literature underlines a potential link between prion diseases, ALS, HD, and neuropsychiatric [41,[43][44][45][46][47][48] Causal link [51][52][53][54][55][56] Vit. D levels ↓ [76][77][78][79] Severity of PD [80][81]83] Genetic link [85][86] Risk factor [96,103] Genetic predisposition [99][100][101] Causal link [109][110][111] / Non-consistent findings [132,133,136] Evidence of genetic link [137] Vit. D levels ↓ [148] Animal and cell culture studies…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent literature underlines a potential link between prion diseases, ALS, HD, and neuropsychiatric [41,[43][44][45][46][47][48] Causal link [51][52][53][54][55][56] Vit. D levels ↓ [76][77][78][79] Severity of PD [80][81]83] Genetic link [85][86] Risk factor [96,103] Genetic predisposition [99][100][101] Causal link [109][110][111] / Non-consistent findings [132,133,136] Evidence of genetic link [137] Vit. D levels ↓ [148] Animal and cell culture studies…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with several previous publications, this is also supported by two recent studies analyzing SNPs in VDR and the vitamin D-binding protein. Besides the functional VDR polymorphism, FokI was reported to be associated with cognitive decline in PD and ApaI with the risk of PD, while vitamin D-binding protein gene was suggested as a risk factor for PD [85,86]. In line with this, a double-blind, placebo-controlled intervention study from Suzuki and colleagues, including 114 PD patients, was able to reveal that supplementation of 1200 IU vitamin D 3 /day prevents disease progression in a VDR FokI genotype-dependent manner [87].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…The Fokl functional VDR polymorphism has been associated with PD and with the cognitive decline in PD (Gatto et al, 2016;Lee et al, 2014;Niu et al, 2015). ApaI, BsmI, and TaqI polymorphisms have not been associated with susceptibility to PD (Lee et al, 2014;Niu et al, 2015).…”
Section: Alad and Vdrmentioning
confidence: 96%
“…The relationship between VDR polymorphisms, vit-D metabolite concentrations and CNS function remains unclear (136) . It has been demonstrated by multiple researchers that expression and functionality of VDR polymorphisms to transactivate specific DNA gene sequences are regulated by both genetics, environment and abundance of bioactive vit-D (128,134,137) . For example, Wilkinson et al (138) observed the TT/Tt VDR genotype of Taq1 polymorphism was associated with tuberculosis in a UK Indian population, but only in a vit-D-deficient state.…”
Section: Vitamin D Receptor Genetic Polymorphisms and Cognitive Functionmentioning
confidence: 99%